Oil of Mesua ferrea L. Seed as a Promising Pharmaceutical Excipient in Lipid Based Nanoformulation - Tapash Chakraborty, Malay K. Das (Journal of Applied Pharmaceutical Science, 2017)
This paper reports the studies on the application of Mesua ferrea L. (nahor) seed oil as a safe pharmaceutical excipient. The nahor seed oil was extracted by hot continuous percolation process using a soxhelt apparatus and analyzed by TLC and LC-MS. The safety profile of the oil was studied by acute toxicity study in a rat model and MTT assay with mouse brain endothelial cells (bEnd.3). The compatibility of the oil with other excipients was studied by DSC and FT-IR analysis.TLC and LC-MS study suggest the oil is composed of fatty acids similar to other USP grade oils. The acute toxicity study and MTT assay suggest the safe use of the nahor oil at the cellular level in the living system. DSC and FT-IR study confirm the compatibility of the oil with the general components of the lipid nanoparticles. This work provides a new dimension to M. ferrea L. seed oil for its safe use in the pharmaceutical formulation.
Keywords: Acute toxicity, Biocompatibility, Messua ferrea L., Nahor seed oil, NLC, Pharmaceutical excipient.